Materials science and advanced technologies in manufacturing II : selected, peer reviewed papers from the 4th International Conference on Materials Science and Engineering (ICMSE 2014), December 27-28, 2014, Jiujiang, China - Liu, X. Q.; Al-Mosawi, Ali I.; Li, B. (Advanced materials research ;, 2015)
Collection of selected, peer reviewed papers from the 4th International Conference on Materials Science and Engineering (ICMSE2014), December 27-28, 2014, Jiujiang, China. The 71 papers are grouped as follows: Chapter 1: Materials Science and Technologies; Chapter 2: Nanomaterials and Technologies; Chapter 3: Metal Materials and Alloys; Chapter 4: Polymer Materials; Chapter 5: Composites and Construction Materials; Chapter 6: Physical Properties of Materials.